Perancangan Digital Enterprise Architect Smart course Pada Industri pendidikan - Kevin Dwi Saputra; Dio Ramadani; Raihan Ambari (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Digital transformation is a challenge for the business world today to transform into a digital company that utilizes information technology to optimize company business processes, for efficiency and effectiveness in company performance with improved operational acceleration to achieve company goals. Education is a massive industry in carrying out technological innovation and improving teaching methods, but it is still separated only by one process in education. The aim of this research is to select, examine and combine the development of collaborative technological innovation with the development of learning models carried out previously, then adapting them into an Enterprise Architect smart course design. The research method used is literature study and observation at educational institutions, especially the skills course industry, so that a comprehensive smart course design can be created, adopting proven learning methods, teaching techniques and technological innovation into a rich diagram model. can be understood by all levels of stakeholders in the company. The result of this research is an Enterprise architecture smart course blueprint with ArchiMate modeling, using a business model canvas (BMC) to describe the business architecture and the TOGAF ADM framework which represents the entire Enterprise design and information technology components to support each process in the business design